An enhanced thermoelectric figure of merit for Sr(Ti0.8Nb0.2)O3 based on a Ruddlesden–Popper-polytype-induced microstructure. Issue 5 (April 2016) - Jerič, Marja; de Boor, Johannes; Jančar, Boštjan; Čeh, Miran
Abstract: Platelet crystals based on Ruddlesden–Popper (RP) polytypes prepared by molten-salt synthesis were used to influence the microstructural development of Nb-doped SrTiO3 (STO;Nb) perovskite and, consequently, to change the thermoelectric properties. Electron microscopy revealed intergrowth of RP-polytypic phases within the STO;Nb solid-solution matrix phase. The morphology of the grains varied from isotropic to anisotropic, containing polytypic faults up to 100 μm in length. Such a microstructure increased the thermoelectric figure of merit by 50% at 650 °C, due to substantially enhanced electrical conductivity, slightly increased Seebeck coefficient and lowered thermal conductivity.